حساب احتمال الخطأ في نظام الاتصال الضوئي الليفي الرقمي (Tishreen University, 2019)
في أنظمة الاتصالات الرقمية بالألياف الضوئية وخلال عملية الاستقبال (الكشف الضوئي) ينتج ضجيج الطلقات، وهو عبارة عن ضجيج غير ثابت، وغير مستقل عن الرسالة الرقمية. وبالتالي فإن عملية تقدير متوسط احتمال الخطأ بوجود ذلك الضجيج، تأثير تداخل الرموز تكون ذات تأثير يجب أخذه بعين الاعتبار. لحساب ذلك الضجيج هناك طريقتان: طريقة EXHAUSTIVE، وطريقة سلسلة GRAM-CHARLIER , إذ يستحسن استخدام الطريقة الثانية عندما يكون عدد التداخلات كبيراً إلى حد ما. يهدف البحث إلى حساب احتمال الخطأ الوسطي في نظام إرسال PAM بوجود تداخلات بالرموز، وسوف نقدم بعض الأمثلة الرقمية من أجل/ إرسال مستقل ثنائي بالرموز / بوصفها أمثلة تطبيقية في هذه المقالة. In digital fiber optic transmission systems and during the photo detection process, a shot noise is produced: it is a type of noise neither stationary nor independent of the digital message. Therefore, the evaluation of both the average error probability, in the presence of such a noise, and the effect of the symbol interference, brings about an impact to be taken into account. This noise can be calculated in two methods: the EXHAUSTIVE and GRAM-CHARLIER series expansion. The latter is preferred, when the number of interfering factors is somehow large. This research aims at calculating the average error probability in the PAM transmission system, including interfering symbols. The current writers will also present some numerical examples of binary independent-symbol transmission as illustrative cases.